TANGGUNG JAWAB PT. PRATAMA MAKMUR JAYA MEDAN TERHADAP BARANG BAWAAN MILIK PENUMPANG DALAM BAGASI BUS MAKMUR - Yerikho Alexandre; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The transport is a transfer of location, both to things and to people, an activity that guarantees passengers on the bus.Prior agreements would need to be established with passenger tickets or transport papers. With tickets to prove the agreement, customers and customers must fulfill their rights and obligations according to the 1999 statute no. 8 on consumer protection. PT. Pratama Makmur Jaya medan was one of the otobus companies. In progress, PT. Pratama Makmur Jaya on transporting both persons and cargo items and passenger packages by attabounding clausen on the condition of the transport agreement that was on the bus ticket to be jointly agreed upon. In practice, passengers have suffered losses caused by the negligence of both the transporters and the passengers themselves. To limit the duty of the transport vessel to make clause on the condition of the transport agreement on their bus ticket that reads